Laboratory course development and implementation fostering teaching assistant growth - R. Telfah; A. Roser; R. Masoud; J. Shultz (Journal of Microbiology & Biology Education)
ABSTRACT STEM teaching assistants (TAs) are vital resources at the university level and are responsible for teaching most undergraduate laboratory courses. TAs are expected to navigate the complex interaction of personal confidence, course goals, varied student preparedness, and instructor supervision while delivering a quality educational experience. These variables combine to create an exceptionally prepared professional, a quick exit from the STEM field, or a capable individual in need of additional training. We present three individual TA development examples spread across three lab courses (Gel Electrophoresis, Genetics, and PCR Methods). Examples of these course materials are included, including links to the instructional resources for each of the three classes.